No Plunging and Cold Maceration followed by No Plunging as Alternative Winemaking Techniques: Tannin Extraction and Pigment Composition of Syrah and Pinot Noir Wines - Chittenden, R.; King, P. (South African Journal of Enology and Viticulture, 2020)
Three different cap management maceration techniques were compared using Syrah (2015) and Pinot Noir (2016). The control, Traditional maceration (TM), of two plunges per day for 15 days total maceration was compared with a No Plunge (NP) trial and a Cold Maceration followed by No Plunge (CM) trial. Total phenolic, tannin and colour extractions were compared during and post maceration using the AWRI WineCloudTM. Differences were noted for both varieties. The Pinot Noir wine CM trial developed higher extractions and more stable colour over time compared with the NP and TM trials. Whereas with the Syrah wine, both the CM and NP trials displayed higher total phenolic, tannin and colour extractions with more stable colour over time compared with the TM trial.